2018
DOI: 10.1016/j.jsams.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Reduced severity of lumbo-pelvic-hip injuries in professional Rugby Union players following tailored preventative programmes

Abstract: Our preliminary observations support the effectiveness of grouping players and tailoring intervention based on common group characteristics in reducing the severity of LPH injuries in professional Rugby Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(29 reference statements)
0
8
0
2
Order By: Relevance
“…'Maintenance' of protective equipment use was not reported in any paper. Studies investigating NMT training programmes [58][59][60][61][62][63][64] had the highest median DB score but all failed to report programme 'maintenance'.…”
Section: Intervention Typesmentioning
confidence: 99%
“…'Maintenance' of protective equipment use was not reported in any paper. Studies investigating NMT training programmes [58][59][60][61][62][63][64] had the highest median DB score but all failed to report programme 'maintenance'.…”
Section: Intervention Typesmentioning
confidence: 99%
“…The research conducted on the hip abductors for LBP has been extensive, with most concluding that strengthening exercises for the hip abductors is beneficial for treating those with LBP. [2][3][4]8,9,12,15,16,25,41,64,67 It is important for clinicians and researchers to be able to determine this strength ratio measurements of the hip abductors to the hip adductors to use as a rehabilitation tool in strengthening the hip musculature in patients with LBP. Knowing strengthening of the hip abductors is essential in treatment of LBP, the hip abductor to hip adductor strength ratio measurement calculated in this study may provide a clinical goal to reach in hip abductor strength for each patient.…”
Section: Chapter V: Discussionmentioning
confidence: 99%
“…2 Previous research has identified treatment options for reducing LBP in different populations, such as utilizing strengthening exercises for hip and trunk musculature. [3][4][5][6] Specifically, a need for increased strength in the hip abductors and abdominals has been shown, [7][8][9][10][11][12][13][14][15] as well as the effects opposing musculature of the hips and trunk have on LBP when not balanced, including the hamstrings, iliopsoas, quadriceps, and back extensor musculature. 8,12,[16][17][18][19] The muscles of the hips and trunk, if overactive or tight, can cause biomechanical changes in the body such as lordosis, kyphosis, and other postural abnormalities.…”
Section: Tablesmentioning
confidence: 99%
See 2 more Smart Citations